Effect of some Organic Fertilizer on Growth, Flowering and Cormels Yield of Gladiolus (Gladiolus Hybrida cv. White prosperity) - نصور, مازن; هيفا, سوسن; قاسم, رنا (Latakia University Journal -Biological Sciences Series, 2022)
A field experiment was conducted to evaluate the influence of adding treated organic residues (olive mill wastewater- OMW, sewage sludge -SS and biochar- B) on growth, flowering and corm production of Gladiolus hybrida cv. White prosperity grown in calcareous soil, in Lattakia, during the seasons 2018-2019 and 2019-2020. The experiment was laid out in a complete blocks design (C.B.D) included 9 treatments with3 replications: (T1: Control, T2: mineral and organic fertilization, T3: adding OMW, T4: adding SS, T5: adding B, T6: adding (OMW+ SS), T7: adding (B+ SS), T8: adding (B+ OMW), T9: adding (B+OMW+SS). A very marked results for all studied vegetative parameters (plant height, leaf number, leaf area, leaf content of total chlorophyll, fresh and dry weight) were recorded in T9( 3,5L\m2 of OMW+ 1,25 Kg\m2 of SS+ 2 Kg\ m2 of B(. All organic fertilization treatments, especially T9, achieved best results regarding all qualitative flowering characteristic (length and diameter of flower stalk, number of flowers per spike, percentage of dry matter and vase life)as compared to control T1 .T9 showed to produce the longest flowering duration. Results also showed that all fertilization treatments were better than the control T1 for all studied vegetative and flowering parameters. The best number of cormels per plant (50,97( and percentage of big cormels that are<1 cm in diameter (17,95%) were achieved by T4(adding 2,5 Kg\m2 of SS( which was significantly better than all other studied treatments.